PRIVACY-CENTRIC DATA WAREHOUSING IN MARKETING: NAVIGATING THE INTERSECTION OF ANALYTICS AND REGULATORY COMPLIANCE - Santhosh Gourishetti, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
In the era of data-driven marketing, organizations face the dual challenge of leveraging vast amounts of consumer data for analytics while adhering to increasingly stringent privacy regulations. This article examines the concept of privacy-first data warehouses as a solution to balance marketing effectiveness with regulatory compliance. We explore the evolution of data warehouses in marketing, analyze the impact of regulations such as GDPR and CCPA, and propose a framework for implementing privacy-centric data infrastructures. Through a combination of technical strategies, including data minimization, purpose limitation, and advanced security measures, alongside organizational approaches like privacy impact assessments and data governance frameworks, we demonstrate how businesses can maintain robust analytics capabilities while prioritizing consumer privacy. Case studies of successful implementations are presented, along with an analysis of challenges and future trends in privacy-enhancing technologies. This article contributes to the growing body of knowledge on ethical data practices in marketing. It provides practical insights for organizations seeking to navigate the complex landscape of big data analytics and privacy compliance.